Value Co-Creation and Digital Marketplace Strategy in Enhancing Commercialization Performance, An Educational Perspective from Fortified Goat Milk Entrepreneurship - Arih Dwi Prihastomo; Nicholas Renaldo; Achmad Tavip Junaedi; Harry Patuan Panjaitan; Nyoto Nyoto; Marice Br Hutahuruk; Umar Faruq; Muhammad Pringgo Prayetno; Yenny Wati; Luciana Fransisca (First Ciera Publisher, 2026)
The rapid transformation of the digital economy has reshaped entrepreneurial practices, particularly within agribusiness sectors that increasingly rely on digital platforms to enhance market reach and competitiveness. This study examines the role of value co-creation and digital marketplace strategy in enhancing commercialization performance from an educational perspective within the context of fortified goat milk entrepreneurship. Using a quantitative explanatory design, data were collected from 156 participants involved in entrepreneurship learning programs integrated with real-world digital commercialization activities. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that value co-creation significantly influences digital marketplace strategy and commercialization performance. Digital marketplace strategy also significantly affects commercialization performance and partially mediates the relationship between value co-creation and commercialization performance. The model demonstrates substantial explanatory power, suggesting that collaborative engagement supported by structured digital systems enhances measurable business outcomes. From an educational perspective, the findings reveal that commercialization performance can function as a practical learning outcome within experiential entrepreneurship education. The study contributes to the literature by integrating service-dominant logic, digital marketing strategy, and entrepreneurship education into a unified framework. It highlights that digital value co-creation is not only a strategic driver of market performance but also a transformative pedagogical approach in technology-enabled agribusiness development.